A sensorimotor enhanced neuromusculoskeletal model for simulating postural control of upright standing - Shanbhag, Julian; Fleischmann, Sophie; Wechsler, Iris; Gassner, Heiko; Winkler, Jürgen; Eskofier, Bjoern M.; Koelewijn, Anne D.; Wartzack, Sandro; Miehling, Jörg (Frontiers in Neuroscience, 2024)
The human's upright standing is a complex control process that is not yet fully understood.Postural control models can provide insights into the body's internal control processes of balance behaviour. Using physiologically plausible models can also help explaining pathophysiological motion behaviour. In this paper, we introduce a neuromusculoskeletal postural control model using sensor feedback consisting of somatosensory, vestibular and visual information. The sagittal plane model was restricted to effectively six degrees of freedom and consisted of nine muscles per leg. Physiological plausible neural delays were considered for balance control. We applied forward dynamic simulations and a single shooting approach to generate healthy reactive balance behaviour during quiet and perturbed upright standing. Control parameters were optimized to minimize muscle effort. We showed that our model is capable of fulfilling the applied tasks successfully. We observed joint angles and ranges of motion in physiological plausible ranges and comparable to experimental data. This model represents the starting point for subsequent simulation of pathophysiological postural control behaviour.